Straits Settlements Blue Book (imports/exports) 1907-1908 vol.47-48 (Great Britain : Public Record Office, 1971)
Mengandungi'Straits Settlements return of imports and exports for the year 1907';'Recapitulatory and comparative statement of the value of imports into and exports from the Straits Settlements for the yearas 1906-1907';'Blue Book for the year 1908'.